2023
DOI: 10.1007/s00214-023-02991-0
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic response functions and Stokes-Einstein breakdown in superheated water under gigapascal pressure

Abstract: Liquid water is the most intriguing liquid in nature, both because of its importance to every known form of life, and its numerous anomalous properties, largely magni ed under supercooled conditions. Among the anomalous properties of water is the seeming divergence of the thermodynamic response functions and dynamic properties below the homogenous nucleation temperature (~232 K). Furthermore, water exhibits an increasingly decoupling of the viscosity and diffusion, upon cooling, resulting in the breakdown of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…For this, we calculate two-dimensional profile of hydrogen (H−)-bond number between water molecules N H ‑ bond , presented in Figure B for COF –3 . An H-bond between two water molecules is defined by the standard criteria, r O D O A < 3.5 Å and ∠H D O D O A < 30°, where “D” and “A” stand for the H-bond donor and acceptor molecules, respectively. As expected, the first hydration layer of the channel wall has lower number of H-bond. At the center of the channel, the number of H-bonds per water molecule is ∼3.6, which is expected for bulk water.…”
Section: Resultsmentioning
confidence: 82%
“…For this, we calculate two-dimensional profile of hydrogen (H−)-bond number between water molecules N H ‑ bond , presented in Figure B for COF –3 . An H-bond between two water molecules is defined by the standard criteria, r O D O A < 3.5 Å and ∠H D O D O A < 30°, where “D” and “A” stand for the H-bond donor and acceptor molecules, respectively. As expected, the first hydration layer of the channel wall has lower number of H-bond. At the center of the channel, the number of H-bonds per water molecule is ∼3.6, which is expected for bulk water.…”
Section: Resultsmentioning
confidence: 82%
“…The previous work was authored by one of us, where the non-Gaussian displacement distribution was observed in a raft mimetic membrane having liquid-ordered (L o ) and liquid-disordered (L d ) phases coexisting together. 127 It was also found that the FnGD behaviour could be explained both by the ''diffusing diffusion'' picture, 184 and the translational jump-diffusion (TJD) model, 127 previously employed to explain the diffusion-viscosity decoupling in supercooled water 130,134,[185][186][187][188][189] and aqueous solution. 131,132,135,136,190 Interestingly, similar FnGD behaviour was not observed for the pure L o and L d phases of the membrane.…”
Section: Lateral Diffusionmentioning
confidence: 99%